Current Status and Surgical Technique for Restorative Proctocolectomy with Ileal Pouch Anal Anastomosis - Melik Kağan Aktaş; Mehmet Gülmez; Ahmet Anıl Sahar; Can Saraçoğlu; Eren Esen; Erman Aytaç; Feza H. Remzi (Balkan Medical Journal, 2023)
Restorative proctocolectomy with ileal pouch-anal anastomosis (RP/IPAA) is the procedure of choice for patients with ulcerative colitis (UC), some patients with colonic Crohn’s disease (CD), and those with familial adenomatous polyposis (FAP); albeit, owing to its complexity, it should be performed by experienced professionals. RP/IPAA is the recommended surgical treatment for UC when the standard medical therapy is ineffective. This procedure has been demonstrated to provide patients with a good quality of life, such as in FAP patients with extensive disease in the rectum. The CD has been associated with higher rates of perianal involvement and disease recurrence, but some patients with CD limited to the large intestine and minimal perianal or ileal disease may also be considered for this operation. First, all patients undergo a detailed preoperative evaluation that includes a review of previous imaging, pathology, and colonoscopy findings, a perianal examination, an evaluation of the anorectal functions, mechanical bowel preparation, and prophylaxis against deep venous thrombosis and infectious complications. A staged approach is the most commonly preferred technique for RP/IPAA, which can be performed in 2 or 3 stages. The IPAA can be performed by laparoscopic, robotic, or open approach. The type of approach is determined based on the patient’s condition, medication used, elective or emergency setting, and the surgeon’s expertise level. A successful IPAA requires tension-free pouch anastomosis. The most common IPAA pouch types are the J or S pouches; alternatively, an H pouch may be created, which is mainly used in redo pouches. In experienced centers, > 95% of the patients become stoma-free in 10 years. IPAA is a complex procedure, and the complications after pouch surgery are pouchitis, pelvic sepsis, pouch failure, or anastomotic stricture. The majority of long-term complications can be prevented in such cases with a comprehensive preoperative evaluation and through the use of appropriate surgical techniques and postoperative care conducted at experienced centers. The techniques for performing RP/IPAA with their long-term outcomes have been reviewed in this article.